Distribution and abundance of the giant clams (Cardiidae: Bivalvia) on Kei Islands, Maluku, Indonesia - TEDDY TRIANDIZA; NEVIATY P ZAMANI; HAWIS MADDUPPA; UDHI E HERNAWAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Triandiza T, Zamani NP, Madduppa H, Hernawan UE. 2019. Distribution and abundance of the giant clams (Cardiidae: Bivalvia) on Kei Islands, Maluku, Indonesia. Biodiversitas 20: 884-892. Giant clams, ecologically important bivalves in coral reefs, are under anthropogenic pressures in most parts of their range, necessitating the study of population status for conservation management. Here, we assessed species composition, distribution, size density, and habitat condition of giant clams in Kei Islands. A total of 9 reefs around the islands (Dar 1, Dar 2, Pulau Kur, Pulau Tanimbar Kei, Pulau Adranan, Pulau Dullah Laut, Difur, Labetawi, dan Ohoidertoom), were surveyed using quadrat-transect line in September-December 2017. We found five species of giant clams, i.e., Tridacna crocea, T. maxima, T. squamosa, T. noae, and Hippopus hippopus. Of these species, we report a new record for T. noae which was previously not known to be present in the region. The overall density was recorded at 0.0428 individual/m2. Juveniles clams were fewer than the adults clam, this may indicate that the survival rate of recruit is low. Most individuals were found living on dead coral algae substrate (75 %). Based on the findings, this study suggests that giant clam population in Kei Islands are imperiled, indicated by low population density and local extinction for species T. gigas and T. derasa. It is recommended to establish a protected area and restocking of giant clams by through implementing sasi laut (traditional law) with a minimum period of 5 years.